The increased effective connectivity from left middle occipital gyrus to right medial septum/diagonal bands in AD patients after donepezil intervention - Yang, Ting; Wei, Fuquan; Guo, Yufei; Zhu, Mengxiao; Hou, Hongtao; Guo, Zhongwei; Liu, Xiaozheng (Frontiers in Aging Neuroscience, 2024)
INTRODUCTION: Donepezil enhances the function of cholinergic nerves by increasing the concentration of acetylcholine, thereby improving clinical symptoms in patients with Alzheimer's disease (AD). However, the neural mechanisms of how donepezil modulates the effective connectivity (EC) network of cholinergic system in AD patients remain unknown. We speculated that the effective network of the cholinergic system changes in AD patients after donepezil intervention. METHODS: We employed resting-state functional magnetic resonance imaging and Granger causality analysis approach to explore changes in the effective connectivity network of the basal forebrain in AD patients before and after donepezil intervention. This study included 32 participants, including 16 healthy controls (HCs) and 16 AD patients. In a 3T MRI scanner, the 16 AD patients were scanned before and after the donepezil intervention. To compare EC differences between the three groups of participants, ANOVA and post hoc t-tests analysis were employed. RESULTS: Compared to baseline status, AD patients after donepezil intervention had an increased EC from left middle occipital gyrus to right medial septum/diagonal bands. Compared to HCs, AD patients after donepezil intervention had an increased EC from right inferior frontal gyrus/orbit part to right medial septum/diagonal bands, AD patients before donepezil intervention had a reduced EC from right precuneus to right medial septum/diagonal bands. A significant positive correlation was found between EC values in right precuneus and Mini-mental State Examination in pre-intervention AD patients (r = 0.7338, p = 0.0012). DISCUSSION: Our study showed that effective connectivity of brain regions associated with the default mode network in the cholinergic pathway was enhanced after donepezil intervention. The results of this study will help us to better understand the neural mechanisms of donepezil intervention in AD and to find clinical targets for intervention.